(untitled) (Journal of Asian Development Studies, 2025)
To overcome the environmental and sustainability challenges caused by agro-wastes, such as wheat straw (Triticum aestivum L.), wheat bran (Triticum aestivum L.), and rice husk (Oryza sativa L.) biotechnological innovations played a vital role. This research focused on the use of lignocellulolytic fungus Aspergillus niger in solid-state fermentation for the cost-effective production of cellulase and pectinase enzymes with agricultural residues as substrates. The evaluation of wheat bran as a substrate for fungal growth revealed the highest fungal cellulase activity and pectinase activity at 6.47 ± 0.35 U/g and 4.03 ± 0.25 U/g, respectively. Wheat bran outperformed other substrates in terms of cellulose and pectinase activity, hence strengthening its position as a fermentation substrate. Moderate enzyme production was shown by rice husk (cellulase activity 3.27 ± 0.25 U/g and pectinase activity 1.90 ± 0.20 U/g). Wheat straw showed the least enzyme activity (1.03 ± 0.15 U/g cellulase and 0.73 ± 0.15 U/g pectinase), likely because high-cellulose fibrous materials slow down enzymatic breakdown of complex structures. These results showed the potential of agro-residues and agro-industrial waste, particularly wheat bran, as substrates for controlled bioprocesses, for the advancement of sustainable byproduct enzyme production and eco-friendly workflows.